Estruturação genética populacional de Salminus hilarii (Characiformes : Characidae) na Bacia do Alto Paraná - Nunes, Aline Galindo (2015)
The Salminus genus is characterized by predatory fish medium to large, migratory and ichthyophagi, very appreciated in fisheries and gastronomy. Among these stands out the Salminus hilarii species, popularly known as tabarana and considered top of the food chain, due to its high degree of selectivity for environments with rich water oxygen which constitutes a good environmental indicator. This species occurs in the São Francisco basins, Paraná basins and Jaguaribe river, and depends on specific hydrological conditions to carry out their reproduction. In this context and because of intense anthropogenic interference that such river systems have suffered, population's study of tabaranas in the upper Paraná basin can contribute to a better understanding of aspects related to its population structure and conservation of their populations. Thus, the aim of this study was to characterize the population genetic structure of S. hilarii at different periods in rivers of the Upper Paraná basin, in order to better understand the population dynamics of fish and effectively contribute to their conservation. It was used for molecular analysis 15 polymorphic microsatellite loci and mtDNA (D-loop). The results revealed the existence of population differentiation among the rivers sampled. Nevertheless, individuals sampled in the Jacaré-pepira river and Cubatão showed no genetic difference, indicating the occurrence of gene flow between populations sufficient to maintain the genetic homogeneity. Moreover, it was possible to identify the temporal structure into the Turvo and Jacaré-pepira river. A high genetic diversity was found in populations of Upper Paraná basin sampled rivers. The D-loop analysis showed no population structure between samples, but indicated the occurrence of a high diversity. The contradictory results may be due to mutational rates of the markers used, since microsatellites have high mutational rate. These results are important for understanding the behavior and biology of these fish, and also to establish fisheries management programs and conservation S. hilarii in the upper Paraná basin.